Current Status of Innovative Technologies Transfer in Russia - Olga PYATAEVA; Oleg SKRYABIN; Valentina BRITVINA; Ekaterina BOBROVA; Galina Konyukhova (Communications of International Proceedings, 2021)
Innovation development of national economy could be realized due to development innovation technology transfer mechanisms. The main indicators of these processes in Russian economy calls for comments. The authors of the article highlight a high priority of improving technology transfer efficiency which has a great impact on improving the quality and performance of innovation infrastructure at whole. This is reflected, for example, in increasing of a share of innovation goods, jobs, services in total exports; in intensifying of technology innovation costs, in aggregating level of innovation activity of organizations and also a number of license contracts and in alienating of patent rights concluded by citizens of Russian Federation, etc. These and other indicators was included in the list of target indicators for implementation of the Innovation Development Strategy of Russian Federation for the period up to 2020. In this case the authors of the article describe statistical characteristics of innovative technologies transfer in Russia in 2013-2020 and formulate conclusions and prospects for development innovation technology transfer mechanisms.
Keywords: Technology transfer; innovation development; innovation technologies; innovation activity.